Bridging the gap in the knowledge on the role of spatial planning in the reduction of wildfire risk: insights from Portugal - Tedim, Fantina (2022)
The 2017 wildfires marked a dramatic milestone in Portuguese society, which corresponded to an extreme intensity and the inherent loss of life, property, and thousands of forest hectares. This high impact led to a paradigm shift regarding prevention and firefighting, highlighting the need for an integrated fire management approach and assuming as imperative the integration of wildfire risk reduction on spatial planning at municipal level. This turning point was expressed in the prolific legislative production, namely in the guidelines for preventing and fighting wildfires, given by the Resolution of the Council of Ministers (RCM) n.Âº 157-A/2017; on the principles set out in the Directive for Preventing and Fighting Wildfires, defined by the RCM n.Âº 20/2018; in the approval of the National Plan for the Integrated Management of Wildfires (PNGIFR), emanated from the RCM n.Âº 45-A/2020, which established the need to implement an Integrated Management System for Wildfires (SGIFR), whose vision and objectives were defined in the RCM n.Âº 12/2019, and its operating rules were enacted in the Decree-Law n.Âº 82/2021. As such, the SGIFR establishes, at a national level, strategic guidelines with a view of risk reduction, changing the behaviour of owners, users and other beneficiaries of the rural territory. In addition, SGIFR proposes integrating wildfire risk reduction in spatial planning through the insertion of fire hazard map, namely in the master planâ€(r)s constraints map (i.e., the map where are identified the administrative easements and public utility restrictions that may constitute limitations or impediments to any specific form of land use). The constraint map is one of the documents of the Municipal Master Plan, i.e., the fundamental legal instrument in the management of the municipal territory that defines the strategic framework for territorial development and the spatial organisation model of the municipal territory. This paper identifies the weaknesses of the approach proposed by the SGIFR to promote wildfire risk reduction through spatial planning, and its short and long-term impacts. Firstly, we used an online questionnaire answered by 18 municipalities from the Centre Region of Portugal, in order to examine the local expertsâ€(r) experience in applying the legislation of spatial planning and wildfire management policies. In a second step, we collected data from a focus group with representatives of the technical forestry office from 8 municipalities where the difficulties, the challenges and needs to integrate spatial planning and wildfire risk reduction were discussed. One of the main weaknesses is related with the integration of the fire hazard map in the constraints map of the Municipal Master Plan, considering the high inter-annual variability of fire hazard and the long-term definition of the municipal development model. This procedure will create building permit constraints which can limit the development and continue to favour the depopulation of the rural areas. This paper contributes to bridging a critical gap in knowledge on the role of spatial planning in the reduction of wildfire hazard and exposure, given the characteristics of fire hazard that are distinctive from other natural hazards (e.g., floods, costal erosion, earthquakes).